An investigation on responsible innovation in the emerging shared bicycle industry: Case study of a Chinese firm - Zheng Liu; Lei Ma; Yue Zhu; Wenchao Ji (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
In the current era of Industrial 4.0, open innovation, and the sharing economy, innovation ecosystems are formed through government-industry-university (triple helix) interaction. The concept of responsible innovation has emerged to explore how innovation can be conducted in a transparent, trustworthy, and sustainable way so as to respond to the public interest. While current literature provides a conceptual framework, details of how responsible innovation can be formed, developed, and sustained in the sharing economy, in particular in developing countries, have been under-explored. This paper aims to explore factors of responsible innovation, linking dimensions with business practice, and identify the dynamic stages of the industry life cycle. Through an in-depth case study of China's shared bicycle industry and the firm Hellobike, this paper has prioritized factors which lead to responsibility, such as user safety and friendliness in product design, real-time operations combined with big data, collaboration between industry and local government for industry standardization, and user credit systems. It has enriched key dimensions based on literature and case studies and proposed dynamic interaction models for industry, government, users, and universities at different stages of responsible innovation in the shared bicycle sector. From this empirical study, future research areas have been identified.
Keywords: 650; China; responsible innovation; sharing economy; triple helix